As nanotecnologias e as Normas ISO: estruturando a governança regulatória por normas técnicas - Martins, Patricia Santos (Universidade do Vale do Rio dos Sinos, 2021)
This Thesis has as its theme "Nanotechnologies and ISO Standards: structuring regulatory governance by technical standards" and takes as its field of study self-regulation and the possibility of protecting already assured rights, such as the right to information, to health, to life, to the environment. It is limited to the scope and action of the ISO standards adopted by Brazil through the ABNT, to identify how they contribute to the protection of these legal assets, in order to observe possible regulatory interfaces between the technical standardization system and the legal system, with the objective of verifying under which conditions the ISO technical standards can be used as alternatives for regulated self-regulation in the development and application of nanotechnology. The NBR ISO 9001:2015, NBR ISO 31000:2018 and NBR ISO 13121:2011 standards are included in the research cutout. The research describes the definitions, characteristics and development of nanotechnologies and their goals. In addition the development from a normative perspective, the existence or not of nanospecific norms in force in Brazil and what would be the existing principles in the legal system for the protection of the rights already protected and the possible interrelationships with the principles and guidelines contained in technical standards - in order to make up for the absence of nanospecific regulatory frameworks. Consequently, the thesis seeks to analyze the concept and effectiveness of self-regulation systems, legal pluralism and the technical standardization system to identify social perceptions regarding possible interfaces. In this sense, an empirical research carried out with the endorsement of the Unisinos Research Ethics Committee, on the possible interrelationships between nanotechnologies, legal principles and technical standards, is part of the thesis. The originality of the thesis can be seen in a search carried out in the Capes theses and dissertations database, searching for expressions: "ISO" type: "thesis - doctorate", area of knowledge: "Law", evaluation area: "Law", area of concentration: “Law and Public Policies”, program name: “Law”. The chosen methodology is the historical and comparative functionalist, which seeks to establish analogies between the various forms of cultural and social organization and, for the human sciences, seeks to emphasize the relationships between various components of a culture or society, and; the empirical research was carried out through the research technique of applying anonymized questionnaires. With the compilation of data, connections will be developed between the theoretical possibilities and the answers found to the empirical research, to highlight the real chances that self-regulatory systems will serve as alternatives for the safe and informative development of disruptive technologies not yet regulated by the state legislative monopoly. In conclusion, a positive result was obtained to establish interfaces between ISO technical standards and Law in order to regulate the scenario of nanotechnological development, which was verified under the theoretical and empirical aspects.
Keywords: Autorregulação; Governança e legitimidade; Pluralismo jurídico normativo; Nanotecnologias; Normas ISO; Self-regulation; Governance and legitimacy; Normative legal pluralism; Nanotechnologies; ISO Standards; ACCNPQ::Ciências Sociais Aplicadas::Direito